Water pump using solar energy to be used in rural areas / Shukri Ishak and Amiruddin Mohd - Ishak, Shukri; Mohd, Amiruddin (Faculty of Mechanical Engineering, 1985)
Energy shortage has become a major problem today, due to the growth consumption limit limiting the research of fossil fuel. Deposits of oil are deficient. Hence, the best alternative source of energy will be the SUN - solar energy, with no polluting qualities and is in abundance. The importance of solar energy today has been known to everybody in their everyday life. In ancient times, the sun provides energy for time, where there is no clocks and watches available. The sun also directs the ways during travelling. The sun-dial was invented based on the existence of the sun. Now, scientists and engineers are making many discoveries on the importance of the sun - solar energy, such as using the solar energy to cook food, using plastic placed directly under the sun to obtain water by condensation. In the future, the solar energy can be fully utilized with proper facilities and techniques, to accommodate the energy shortage, i.e., the shortage of oil deposits.